Plasma B-type natriuretic peptide concentration is independently associated with kidney function decline in Japanese patients with chronic kidney disease. Issue 4 (April 2016) - Yoshitomi, Ryota; Nakayama, Masaru; Sakoh, Teppei; Fukui, Akiko; Shikuwa, Yui; Tominaga, Mitsuhiro; Tsuchihashi, Takuya; Tsuruya, Kazuhiko; Kitazono, Takanari
Abstract : Background and objective: The relationship between B-type natriuretic peptide (BNP) concentration and renal outcomes in patients with chronic kidney disease (CKD) remains unclear; therefore, it has not been determined whether BNP is related to renal outcomes, independent of cardiac parameters. This study was designed to clarify whether BNP concentration is associated with renal outcomes in CKD patients, independent of cardiac functional and structural alterations. Methods: This prospective observational study included 372 consecutive patients with CKD. The renal endpoint was the composite of doubling of serum creatinine concentration and end-stage renal disease requiring dialysis. BNP concentrations were divided into quartiles. A Cox proportional hazards model was utilized to determine the risk factors for poor renal outcomes. Results: During a median follow-up of 23.1 months, the renal endpoint was observed in 124 patients, including 14, 18, 37 and 55 patients in the first through fourth BNP quartiles, respectively. After adjustment for covariates, including cardiac parameters such as left atrial diameter, left ventricular mass index, left ventricular ejection fraction, and left ventricular hypertrophy, the hazard ratios (HRs) for renal outcomes became progressively higher for the second [HR, 1.50; 95% confidence interval (CI), 0.70–3.30), third (HR, 2.29; 95% CI, 1.11–4.91), and fourth (HR, 4.29; 95% CI, 2.05–9.39) BNP quartiles when compared with the lowest BNP quartile. Conclusion: Higher BNP levels were associated with adverse renal outcomes, independent of cardiac structure and function, suggesting that BNP may be a useful biomarker for exploring factors associated with kidney disease progression. Abstract : Supplemental Digital Content is available in the text